Perencanaan Rainwater Harvesting System Dengan Metode Roof Catchment (Studi Kasus: Gedung 8, Institut Teknologi Nasional, Bandung) - Rahmawaty, Annisa’; P, Aryl Tri; R, Ghifari Salman; S, Hisyam Azmi; P, Ilham Dwi; N, Salsabila Putri; F, Salsya Aliya (Dampak, 2022)
The Rainwater Harvesting System Development Planning which will be built using the Roof Catchment method in Building 8 Campus of the National Institute of Technology is an effort to implement policies for soil conservation, collecting rainwater so that it can be reused and participating in environmental protection and planning. The data needed in planning the Rainwater Harvesting System is data on water needs, rainfall, active student data and the existing condition of the building which will later be planned for the Rainwater Harvesting System. After doing the calculations, it was found that the water needs of students in building 8 is 1,168.8 m3/month, the tank volume is 11,159.39 m3 with a depth of 2 m and a tank width of 2.4 m, rainwater discharge is 134,564 m3/s, and dimensions gutter signs of 9 m with a length of 22 m as many as 4 (four) gutters. The construction of the Rainwater Harvesting System is expected to be an alternative in minimizing the use of uncontrolled groundwater and utilizing rainwater as a substitute when the dry season comes. Planning for the Rainwater Harvesting System in Building 8 of the National Institute of Technology requires a cost of Rp. 63,522,000.00 Keywords: Rainwater Harvesting System, Roof Catchment, GutterA B S T R A K Perencanaan Pembangunan Rainwater Harvesting System yang akan dibangun dengan metode Roof Catchment di Gedung 8 Kampus Institut Teknologi Nasional merupakan upaya dalam pelaksanaan kebijakan untuk konservasi tanah, menampung air hujan agar dapat digunakan kembali serta peran serta dalam perlindungan dan perencanaan lingkungan hidup. Data yang dibutuhkan dalam perencanaan Rainwater Harvesting System adalah data kebutuhan air, curah hujan, data mahasiswa aktif serta kondisi eksisting bangunan yang nantinya akan direncanakan Rainwater Harvesting System-nya. Setelah dilakukan perhitungan maka didapatkan bahwa kebutuhan air mahasiswa di gedung 8 sebesar 1.168,8 m3/bulan, volume tangki sebesar 11.159,39 m3 dengan kedalam 2 m dan lebar tangki 2,4 m, debit air hujan sebesar 134,564 m3/det, dan dimensi talang rambu sebesar 9 m dengan panjang 22 m sebanyak 4 (empat) talang. Pembangunan Rainwater Harvesting System diharapkan dapat menjadi salah satu alternatif dalam meminimalisir penggunaan air tanah yang tidak terkontrol dan memanfaatkan air hujan sebagai pengganti disaat musim kemarau datang. Perencanaan Rainwater Harvesting System di Gedung 8 Institut Teknologi Nasional memerlukan biaya sebesar Rp. 63.522.000,00 Kata Kunci: Rainwater Harvesting System, Roof Catchment, Talang